The Selective Inscribing of Laws and Decrees in Late Classical Athens - Lambert, Stephen (Hyperboreus, 2017)
On the basis of a comparison between the extant inscribed Athenian laws and decrees of 352/1–322/1 BC and the laws and decrees proposed by Demosthenes, which fall within the same temporal parameters, but are mainly known from the literary record, this paper argues that, contrary to a position adopted in a recent article by Michael Osborne, only a selection of laws and decrees were inscribed on stone. Some categories of decree were not usually inscribed at all, e.g. those relating to the disposition of forces and other ephemeral matters, and even within the most common inscribed category, the honoriﬁc decree, there were types that were not usually inscribed (e.g. decrees awarding crowns, but no enduring honours and privileges, to foreigners). From the end of the ﬁfth century copies of laws and decrees were deposited in the state archive in the Metroon. The validity of some types of decree, such as treaties, was traditionally so intimately connected with the inscriptions carrying them that it is possible that they continued invariably to be inscribed even after the introduction of the archive. However, the existence of the archive, which originated at the same time as the systematic revision of Athenian law at the end of the ﬁfth century, and may have been designed in the ﬁrst place as a repository speciﬁcally for the laws, may help explain why so few laws were inscribed in the fourth-century democracy.